Penerapan Model Project Based Learning terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas VII UPTD UPF SMP Negeri 1 Kecamatan Aceh Singkil - Fitri Handayani; Mimi Rosadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was motivated by students' low proficiency in writing descriptive essays, characterized by difficulties in developing ideas, organizing paragraphs systematically, selecting appropriate vocabulary, and applying the General Guidelines for Indonesian Spelling (PUEBI). To address these issues, the Project-Based Learning (PjBL) model was implemented. This study aimed to (1) describe the implementation of the Project-Based Learning model in descriptive essay writing instruction and (2) determine its effect on students' descriptive writing skills. A quantitative approach with a Pre-Experimental One-Group Pretest–Posttest Design was employed. The study involved 30 seventh-grade students of SMP Negeri 1 Singkil, Aceh Singkil Regency. Data were collected through pretest and posttest writing assessments, observation, and documentation and analyzed using descriptive statistics. The findings showed that the Project-Based Learning model was implemented according to its instructional stages, including essential questioning, project planning, scheduling, project implementation, project assessment, and learning evaluation. Students actively participated in observation, group discussions, project development, presentations, and reflection. The average writing score increased from 64.67 in the pretest to 84.40 in the posttest, with learning mastery improving from 0% to 100%. Improvements were observed in content, organization, vocabulary, grammar, spelling, and punctuation. The study concludes that the Project-Based Learning model positively improves students' descriptive writing skills by promoting active, collaborative, contextual, and learner-centered learning.